2014
DOI: 10.3109/09638288.2014.933896
|View full text |Cite
|
Sign up to set email alerts
|

Parent management of the school reintegration needs of children and youth following moderate or severe traumatic brain injury

Abstract: Purpose School reintegration following children’s traumatic brain injury (TBI) is still poorly understood from families’ perspectives. We aimed to understand how both unique and common experiences during children’s school reintegration were explained by parents to influence the family. Methods Data came from an investigation using descriptive phenomenology (2005–2007) to understand parents’ experiences in the first 5 years following children’s moderate to severe TBI. Parents (N = 42 from 37 families in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 35 publications
3
47
0
Order By: Relevance
“…Current Return to Learn research cautions against returning students to too much cognitive exertion too quickly 25 . However, this does not mean students should remain at home for extended periods of time because school absence for any reason can have deleterious effects 25‐27 . The consensus results align with literature suggesting that Return to Learn must be individualized and exact recovery cannot be pre‐determined.…”
Section: Discussionsupporting
confidence: 52%
“…Current Return to Learn research cautions against returning students to too much cognitive exertion too quickly 25 . However, this does not mean students should remain at home for extended periods of time because school absence for any reason can have deleterious effects 25‐27 . The consensus results align with literature suggesting that Return to Learn must be individualized and exact recovery cannot be pre‐determined.…”
Section: Discussionsupporting
confidence: 52%
“…In prior studies, both parents and students report that support from teachers, increased knowledge among educators, and understanding the need for and importance of educational modifications, are critical for educational success following ABI. 2224 Echoing these needs, our study observed that the largest proportion of BrainSTEPS team members’ time was dedicated to in-school activities, including consultation with and training of school personnel regarding educational modifications and communication with school personnel. These data may reflect limitations in the preservice and in-service knowledge and skills of educators regarding needs of students with ABI.…”
Section: Discussionmentioning
confidence: 93%
“…Families require effective and extensive communication regarding educational activities and developing comprehensive plans for school reintegration and success. 24, 29, 30 A unique opportunity exists for professionals, such as BrainSTEPS team members, to work with families to identify areas of academic concern with the goal of facilitating effective collaboration within the educational system.…”
Section: Discussionmentioning
confidence: 99%
“…Initiating a parent‐school partnership to develop the best transition to school for a child with a TBI can be difficult. It requires a receptive school environment and a parent who recognizes her/his child's needs and is knowledgeable about the school system and its resources . However, this is not the case for the majority of Hispanic parents.…”
Section: Discussionmentioning
confidence: 99%